2010
DOI: 10.1007/s00381-010-1171-5
|View full text |Cite
|
Sign up to set email alerts
|

Pilomyxoid astrocytoma of the cervical spinal cord in a child with rapid progression into glioblastoma: case report and literature review

Abstract: This is the fifth pediatric spinal cord PMA in literature. Furthermore, it is the only documented patient with rapid recurrence and progression within 3 months into a glioblastoma. The question of a sampling error affecting initial pathology is raised. Based on contemporary literature data, we discuss the further treatment options, as there are no guidelines yet. Efforts towards registries should be encouraged, as the documentation of PMA might lead to more evidence based treatment strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
15
0
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 37 publications
2
15
0
2
Order By: Relevance
“…PMAs are most commonly located in the chiasmal or hypothalamic region, but may occur anywhere along the neuraxis [3,8,9]. They rarely occur in the basal ganglia, parietal and occipital lobes [10], spinal cord [11,12,13], and posterior fossa [14,15]. They have rarely been reported in the temporal lobes [16].…”
Section: Discussionmentioning
confidence: 99%
“…PMAs are most commonly located in the chiasmal or hypothalamic region, but may occur anywhere along the neuraxis [3,8,9]. They rarely occur in the basal ganglia, parietal and occipital lobes [10], spinal cord [11,12,13], and posterior fossa [14,15]. They have rarely been reported in the temporal lobes [16].…”
Section: Discussionmentioning
confidence: 99%
“…The patient subsequently underwent chemotherapy with cisplatin and etoposide, and interval MRI studies revealed no evidence of tumor progression at the time of last followup, 64 months after symptom onset. Paraskevopoulos et al 13 reported a case of a 12year old girl who presented 3 months after a neartotal resec tion of a PMA with glioblastoma multiforme transforma tion and an acute neurological decline. Despite surgery and chemotherapy, she died 1 year after diagnosis.…”
Section: ) Komotar Et Almentioning
confidence: 99%
“…6 To date there have been fewer than 10 cases of spinal PMA reported in the pediatric literature. 2,6,11,13 Even more rare is the presence of extraneural lesions, of which only 1 case has been reported. 2 We review the case of a previously healthy 11-yearold boy with back pain and rapidly progressive scolio sis who was found to have a thoracic spinal cord PMA.…”
mentioning
confidence: 99%
“…En este grupo, el APM es un subtipo poco frecuente que presenta características diferenciales, tanto clínicas como anatomopatológicas. Descrito por primera vez en 1999 2 , existen pocos casos en la literatura 3,4 . Los APM presentan un comportamiento más agresivo, con un menor periodo libre de progresión tras el tratamiento y una supervivencia global más reducida que otros subtipos histológicos de astrocitoma.…”
unclassified
“…Los APM presentan un comportamiento más agresivo, con un menor periodo libre de progresión tras el tratamiento y una supervivencia global más reducida que otros subtipos histológicos de astrocitoma. Registran mayor número de recurrencias y una mayor frecuencia de diseminación en el líquido cefalorraquídeo frente a los astrocitomas pilocíticos típicos 3,4 .…”
unclassified